2022
DOI: 10.1007/s10661-022-09854-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest cover pattern on water quality of low-order streams in an agricultural landscape in the Pirapora river basin, Brazil

Abstract: Low-order streams are important regions for river formation and are highly vulnerable to changes in terrestrial systems. Thus, the land-use/land-cover plays an important role in the maintenance of water quality. However, only its composition may not explain the spatial variation in water quality, because it does not consider landscape con gurations. In this context, the study aimed to evaluate the forest cover pattern effects on water quality on low-order streams, which integrated an agricultural landscape. Ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…As such, rivers have natural productivity pulses to which communities respond by trophic interactions and abundance adjustments (Connell and Ghedini, 2015). In the Andalién River basin, productivity may have increased due to the continuous nutrient inputs from agriculture and forestry and the increased frequency of non-natural forest fires resulting from monoculture with highly inflammable exotic species like Pinus and Eucalyptus (Arriagada et al, 2019;de Mello et al, 2022). Recruitment mechanism includes both habitat connectivity and species dispersal ability.…”
Section: Discussionmentioning
confidence: 99%
“…As such, rivers have natural productivity pulses to which communities respond by trophic interactions and abundance adjustments (Connell and Ghedini, 2015). In the Andalién River basin, productivity may have increased due to the continuous nutrient inputs from agriculture and forestry and the increased frequency of non-natural forest fires resulting from monoculture with highly inflammable exotic species like Pinus and Eucalyptus (Arriagada et al, 2019;de Mello et al, 2022). Recruitment mechanism includes both habitat connectivity and species dispersal ability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while this study dealt with simple compositional land cover metrics (e.g., proportions natural vegetation at various scales), several studies have found that the arrangement of land cover (i.e., landscape configuration) may also influence water quality. It is commonly assumed, for instance, that as natural vegetation cover becomes increasingly fragmented, its ability to trap and intercept surface runoff is reduced (Gergel et al, 2002;Ding et al, 2016;Lintern et al, 2018;Liu & Yang, 2018;Yirigui et al, 2019;Zhang et al, 2019;Cole et al, 2020;Thomas et al, 2020;de Mello et al, 2022;Bowes et al, 2023;Xu et al, 2023a). Therefore, when designing and implementing strategies to protect water quality by maintaining sufficient areas of natural vegetation within riparian areas and across catchments, it is recommended that the potential effects of landscape fragmentation be given due consideration.…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…To this end, decades of research and literally hundreds of independent studies have demonstrated that relatively simple statistical models can be effective tools that support informed decision-making when developing integrated management plans (du Plessis et al, 2015;Giri & Qiu, 2016;Rodríguez-Romero et al, 2018;Ullah et al, 2018;Lacher et al, 2019;Cheng et al, 2022;Li et al, 2022a;Gobry et al, 2023). These studies show that while the relationship between LULC and water quality is undeniably complex and often regionally specific, certain anthropogenic classes of LULC (e.g., built-up areas, farmland, mines, and forestry plantations) tend to be sources of diffuse pollution, whereas most classes of natural vegetation (e.g., indigenous forests, grasslands, and wetlands) serve as sinks by intercepting, filtering, and remediating contaminated runoff (Lintern et al, 2018;Fernandes et al, 2021;Wang et al, 2021;Cheng et al, 2022;de Mello et al, 2022;Li et al, 2022b;Caldwell et al, 2023;Qiu et al, 2023;Siqueira et al, 2023;Xu et al, 2023a;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on land cover effects on water quality have been conducted at several spatial scales, mainly to evaluate different predictors of water contaminants for management purposes [94]. Catchment scale [100], buffer zones [101], circular buffers [28], and distance-weighted approaches [27] have been adopted in numerous studies, which have modeled the spatial variability of biogenic compounds, oxygen indices, and trace metals [53,94]. There are no unified conclusions about the most informative spatial scale, as in some studies the whole catchment is the key to understanding some of the water quality parameters [102,103].…”
Section: The Role Of Spatial Scale For Water Qualitymentioning
confidence: 99%